Casein kinase 2 attenuates brain injury induced by intracerebral hemorrhage via regulation of NR2B phosphorylation - Sun, Zhimin; Li, Qiyao; Li, Xiaopeng; Shi, Yunpeng; Nan, Chengrui; Jin, Qianxu; Wang, Xiaoyan; Zhuo, Yayu; Zhao, Zongmao (Frontiers in Cellular Neuroscience, 2022)
Objective: Intracerebral hemorrhage (ICH) is a common cerebrovascular disease with high incidence rate, disability and mortality. Casein kinase 2 (CK2) is a serine / threonine kinase with hundreds of identified substrates and plays an important role in many diseases. This study aimed to explore the role of CK2-mediated NR2B phosphorylation in neuronal apoptosis, inflammation, and oxidative stress after ICH. Methods: CK2 expression level of brain tissues taken from ICH patients was determined by immunoblotting. Neurons from embryonic rat and astrocytes from newborn rats were cultured and treated by Hemin. The proliferation of astrocytes, the apoptosis and oxidative stress of neurons and the inflammatory factors of astrocytes were detected. CK2 expression was determined in ICH model rats. The effects of pc-CK2 on neurobehavioral defects, brain water content and neuronal damage in ICH rats were observed. Results: CK2 expression in ICH patients was down-regulated. Overexpression of CK2 promoted the astrocyte proliferation, inhibited neuronl apoptosis, and reduced astrocyte-mediated inflammation. NR2B reverse these effects of pc-CK2 on neurons and astrocytes. CK2 phosphorylated NR2B at S1480 site, down-regulated the expression of NR2B and interfered with the interaction between NR2B and PSD95. In vivo experiments showed that the expression of CK2 decreased and the expression of NR2B increased in ICH rats. Furthermore, pc-CK2 attenuated neurobehavioral defects, brain water content and neuronal damage in ICH rats. Conclusion: CK2 phosphorylated NR2B, down-regulated the expression of NR2B, interfere with the interaction between NR2B and PSD95, alleviate inflammatory reaction, inhibit neuronal apoptosis and oxidative stress after intracerebral hemorrhage. CK2 and NR2B may be new potential therapeutic targets for the treatment of intracerebral hemorrhage.